What is Enhanced Recovery After Surgery: Humanity or Technology? - Guowei CHE (Chinese Journal of Lung Cancer, 2018)
The development of surgical techniques and the innovation of surgical instruments promote the changes in surgical methods, which in turn, leads to the reforms of surgical idea. The concept of enhanced recovery after surgery (ERAS) results in the surgery connotation switching from "to treat an illness" to "to save patients". ERAS also causes the change of surgery denotation from "only operation" to "enhance recovery". The concept of ERAS is derived from but not only restricted to the development of surgical techniques. Also, ERAS pays more attention to patients than disease and thinks more about patient safety and recovery than surgical technique. Specifically, ERAS has three advantages: first, ERAS attaches importance to multidisciplinary assessment (patient-oriented) and select appropriate (personalized) treatment and tries to decrease the rate of complication and mortality. Second, ERAS pays attention to preoperative preparation and high-risk prevention performed by multi-disciplinary collaboration in order to prevent complication and save cost for patients. Third, ERAS always focus on optimizing the process of perioperative period and trying to change the working habits of surgeons and the old cooperation mode among doctors, nurses and rehabilitation physicians. To sum up, the goal is to apply the concept of ERAS to all the links of perioperative period and try hard to decrease patients' stress and pain, which finally helps doctors fulfill the ultimate aims of "no pain and no risk".